2011
DOI: 10.1097/tp.0b013e318221d407
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Diphosphate Receptor P2Y12-Mediated Migration of Host Smooth Muscle-Like Cells and Leukocytes in the Development of Transplant Arteriosclerosis

Abstract: Thus, the P2Y12-mediated migration of host-derived SMLCs and CD45+ leukocytes may play an important role in the development of TA, partly by MCP-1 pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Migration facilitated by the activation of P2Y 2 receptors involved the ERK1/2 as well as the arrestin2 pathway [54,58]. Interestingly, migration induced by P2Y 12 receptor stimulation has been proposed to play a major role in transplant arteriosclerosis [57]. In agreement with that Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Migration facilitated by the activation of P2Y 2 receptors involved the ERK1/2 as well as the arrestin2 pathway [54,58]. Interestingly, migration induced by P2Y 12 receptor stimulation has been proposed to play a major role in transplant arteriosclerosis [57]. In agreement with that Fig.…”
Section: Discussionsupporting
confidence: 86%
“…α,β-methylene-ATP inhibited with a halfmaximal concentration of about 0.1 μM the migration of the cells. P2Y receptors including the P2Y 2 , P2Y 6 , and P2Y 12 subtypes mediate the opposite effect-an increase in migration [54][55][56][57][58][59]. Migration facilitated by the activation of P2Y 2 receptors involved the ERK1/2 as well as the arrestin2 pathway [54,58].…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews discuss the use of anti-platelet drugs for the treatment and prevention of CAD [762,764,765]. It has been suggested that ADP-mediated migration of host smooth muscle-like cells and CD45 + leukocytes, via P2Y12R, may play a role in the development of transplant arteriosclerosis, partly by monocyte chemoattractant protein-1 [766]. Clinical trials with clopidogrel and ticlopidine in patients with CAD have shown significant benefit compared with aspirin.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…P2Y 12 −/− mice and mice treated with clopidogrel displayed reduced neointima formation in the wild-type grafted vessel with a reduction of infiltrating host-derived smooth musclelike cells and leukocytes. 10,41 Selective platelet depletion did not inhibit transplant atherosclerosis, suggesting involvement of the P2Y 12 receptors expressed on these host-derived smooth muscle-like cells and leukocytes, including DCs, possibly through a contribution to the migration of these cells.…”
Section: P2y 12 Receptor In Inflammationmentioning
confidence: 99%
“…8,9 The expression of the P2Y 12 receptor was long thought to be restricted to platelets and subregions of the brain. However, it has now been shown that this receptor is also expressed on vascular smooth muscle cells (VSMCs) 10,11 and dendritic cells (DCs). 12 On blood platelets, the P2Y 12 receptor is entirely responsible for the role played by ADP in the amplification of aggregation, secretion, and stabilization of platelet aggregates and in enhancement of the procoagulant activity induced by agonists, such as thrombin, collagen, or thromboxane A 2 .…”
Section: Platelet P2y 12 Receptormentioning
confidence: 99%